Faktor – faktor yang Berhubungan dengan Perilaku Tidak Aman pada Karyawan Departemen Produksi : Studi Kasus : PT X Bekasi Jawa Barat 2019 - Anto Maryadi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The environment and the information gained from the K3 training program's outcomes indicate that the organisation failed to effectively deliver the K3 message, which in turn leads to unsafe actions by employees. There will be a direct correlation between the amount of workplace insecurity and the amount of occupational safety and health training and information that organisations supply. In order to achieve high levels of output and productivity, it is necessary to employ and maintain work equipment and machinery that are both efficient and conducive to high levels of safety (Suma'mur, 2001). Cases of workplace accidents (HH) in Indonesia display graphs that exhibit fluctuations. According to the Social Security statistics from 2016–2018, 110,285 families were able to verify this in 2015. There were 101,367 families in 2016. Additionally, 123,000 HHs were recorded in 2017. There was an increase of 173,101 HHs in the number of work accidents in 2018. Despite a steady rise, its number fell to 101,367 households in 2016 (BPJS Labour, 2019). The purpose of this research is to identify risk factors for risky behaviour among 2019 PT X, Bekasi - West Java manufacturing department personnel. This study employed a quantitative approach based on cross-sectional research. The sample consisted of sixty employees from the manufacturing department, and data was analysed using the Chi-Square test. According to the findings, a significant number of employees exhibit unsafe behaviour. Additionally, a considerable number of employees are young, with a total of 54 employees (90%) having completed both elementary and secondary education. Among these employees, 21 (35%) exhibited low knowledge, 22 (36.7% attitude), and 21 (35%) K3 training. No correlation was found between age and unsafe action (p-value = 0.519, p-value > 0.05), education and unsafe action (p-value = 1,000, p-value > 0.05), knowledge and unsafe action (p-value = 0.774, p-value > 0.05), attitude and unsafe action (p-value = 0.507, p-value > 0.05), and training and unsafe action (p-value = 0.048, p-value > 0.05).